FROM ATTACHMENT TO GELASSENHEIT: A HEIDEGGERIAN PHENOMENOLOGICAL ANALYSIS OF ARJUNA'S CRISIS IN THE BHAGAVAD GITA - Rifqi Khairul Anam (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Arjuna's crisis in the Bhagavad Gita is often interpreted as a moral or theological dilemma, yet this overlooks the profound psychological suffering depicted. This article re-examines this crisis not as a moral failure, but as a phenomenological portrait of absolute Attachment, a condition of painful enmeshment in the worldly web of relations. A Heideggerian phenomenological analysis is employed, using a close reading of the Gita's first chapter to diagnose the lived experience of Attachment and juxtaposing it with Martin Heidegger's concept of Gelassenheit (releasement). The analysis reveals Arjuna's paralysis as a direct symptom of his entrapment in calculative thinking (rechnendes Denken) born from Attachment. In contrast, Gelassenheit is presented as a meditative path of releasement (besinnliches Nachdenken) that allows one to act within the world without being ontologically consumed by it. The concept of Gelassenheit thus emerges as a powerful existential framework for understanding and responding to the specific suffering caused by Attachment, providing a bridge for a fruitful dialogue between an ancient Eastern narrative and modern Western phenomenology.